Young adults Undergoing Coronary Artery Bypass Grafting (CABG) - Muhammad Arif; Saleem, Yusra; Riaz, Stephen; Mahapara; Muhammad Imran; Sharjeel, Atif; Ali Khan, Shujjaat; Ghufran Ullah Khan (International Journal of Endorsing Health Science Research, 2020)
Background: Coronary artery bypass grafting (CABG) is referred to as the gold standard therapeutic modality for treating coronary artery disease (CAD) among both old or young patients. hypertension, diabetes, Increased BMI and obesity, etc. are among the major risk factors for the development of cardiovascular diseases. The aim of the current study was to highlight the increasing rate of CAD and associated CABG surgery among young adults and to identify the potential risk factors associated with it. Methodology: In this hospital based observational study, CAD patients ≤40 years of age admitted to the cardiac surgery department of a leading cardiac center for CABG surgery were included in the study. The study continued from 5th January 2018 to 21st August 2019 and the data of 184 patients who underwent CABG was collected during this time period. The details regarding patients' age, weight, height and body mass index (BMI) were obtained at the time of initial examination. Moreover, medical records, familial history and risk profile were also monitored. The collected data was analyzed using SPSS Version 22.0. Results: A total of 184 CAD patients who underwent CABG surgery were included in the study and 114(62%) of them were males and 70(38%) were females. The age range was 25 to 40 years with the mean age of 36.5±3.17 years. The risk profile displayed that increased BMI was the major contributor for cardiovascular disease i.e. 38% patients were overweight, 10.9% were in Obese I category and 5.97% were in obese II category. Following obesity, hypertension (49.5%), diabetes (29.9%) and dysfunctional lipids (14.7%) were common comorbid conditions. While smoking and positive familial history also contributed to the risk ratio. It was observed that hypertension, diabetic history was more among overweight and obese individuals (p=0.029 & 0.666). Conclusion: Young CAD patients ≤40 years of age display decreased risk and adverse outcomes as compared to the older counterparts but the clinical pattern of presentation is different and hence require different strategic attention.